In silico design of novel bioactive molecules to treat breast cancer with chlorogenic acid derivatives: a computational and SAR approach - Sehrawat, Renu; Rathee, Priyanka; Rathee, Pooja; Khatkar, Sarita; Akkol, Esra Küpeli; Khatkar, Anurag; Sobarzo-Sánchez, Eduardo (Frontiers in Pharmacology, 2023)
Cancer is a vast group of diseases when abnormal cells multiply and grow uncontrollably and it is one of the top causes of death globally. Several types of cancer are diagnosed, but the incidence of breast cancer especially in postmenopausal women, is increasing daily.Chemotherapeutic agents used to treat cancer, are generally associated with severe side effects on host cells, which led to a search for safe and potential alternatives. Therefore, the present research has been conducted to find novel bioactive molecules to treat breast cancer with chlorogenic acid and its derivatives. Chlorogenic acid was preferred because of its known activity in the field. A series of chlorogenic acid derivatives were subjected to computational studies such as molecular docking, ADME, drug-likeness, toxicity, and pass prediction to develop a potential inhibitor of breast cancer. The PDB ids used for docking purposes were 7KCD, 3ERT, 6CHZ, 3HB5, and 1U72. Exhaustive analysis of results has been conducted by considering various parameters like docking score, binding energy, types of interaction with important amino acid residues in the binding pocket, ADME, and toxicity data of compounds. Among all the selected derivatives, CgE18, CgE11, CgAm13, CgE16, and CgE9 have astonishing interactions excellent binding energy, and better stability in the active site of targeted proteins. The docking score of compounds CgE18 was -11.63 kcal/mol, -14.